2018
DOI: 10.7287/peerj.preprints.26948
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Foraging dynamics are associated with social status and context in mouse social hierarchies

Abstract: Living in social hierarchies requires individuals to adapt their behavior and physiology. We have previously shown that male mice living in groups of 12 form linear and stable hierarchies with alpha males producing the highest daily level of major urinary proteins and urine. These findings suggest that maintaining alpha status in a social group requires higher food and water intake to generate energetic resources and produce more urine. To investigate whether social status affects eating and drinking behaviors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Living in a group bears many advantages that increase evolutionary fitness, such as mutual protection, assistance in resource acquisition, and more mating opportunities [ 1 , 2 ]. However, it also carries some costs, such as having to share valuable resources and the need to fight for one's social ranking [ 3 ]. Above all costs, social species endure life-threatening stress in the case of forced social isolation [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Living in a group bears many advantages that increase evolutionary fitness, such as mutual protection, assistance in resource acquisition, and more mating opportunities [ 1 , 2 ]. However, it also carries some costs, such as having to share valuable resources and the need to fight for one's social ranking [ 3 ]. Above all costs, social species endure life-threatening stress in the case of forced social isolation [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the former example, animals exhibiting the highest number of offensive behaviors toward their own cagemates are considered dominant, 69 whereas in the resident-intruder model, animals exhibiting the highest number of offensive behaviors toward the intruder are considered dominant. 21,70 Analysis of spontaneous agonistic interactions and evaluation of wounds or barbering among cagemates has been conducted in group-housed male mice, 16,27,28,30,33,38,39,46,69,[71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90] female mice, 16,38,39,86,91,92 male rats, 4,14,[22][23][24]31,32,34,[93][94]…”
Section: Agonistic Behaviorsmentioning
confidence: 99%
“…For example, it has been repeatedly shown that dominant male rats (based on exhibition of agonistic behaviors) consume significantly more food/water and have more frequent bouts of consumption than their subordinate cagemates. [5][6][7][8] Based on these previous findings, a study by Lee and colleagues 90 analyzed patterns of food and water intake in male mice of differing social ranks. They found that mice considered dominant based on exhibition of agonistic behaviors had a significantly higher number of eating and drinking bouts than subordinates.…”
Section: Foragingmentioning
confidence: 99%
See 1 more Smart Citation
“…S6. for the David's score of each individual in the study) as previously described in Lee et al 23,85,86 . Based on David's scores (on group housing Day 6), we selected two urine donors per cohort (alpha = the highest David's score in the group, the most subordinate = the lowest David's score).…”
Section: Group Dominance Structure Emergence Of Hierarchies and Indimentioning
confidence: 99%